Mitochondrial PCR-RFLP Assay to Distinguish Triatoma brasiliensis macromelasoma from Triatoma brasiliensis brasiliensis Subspecies (Hemiptera: Reduviidae) - Daniel Pagotto Vendrami; Walter Ceretti-Junior; Marcos Takashi Obara; Mauro Toledo Marrelli (Journal of Tropical Medicine, 2013)
Triatoma brasiliensis sensu lato (s.l.), the main vector of Chagas disease in northeastern Brazil, is a species complex comprising four species, one with two subspecies (T. brasiliensis brasiliensis, T. brasiliensis macromelasoma, T. juazeirensis, T. sherlocki, and T. melanica), and each taxon displaying distinct ecological requirements. In order to evaluate the genetic relationships among nine T. brasiliensis s.l. populations from northeastern Brazil, we analyzed their mitochondrial cytochrome c oxidase subunit 1 sequences and suggested a PCR-RFLP assay to distinguish between T. b. macromelasoma and T. b. brasiliensis subspecies. All the specimens were morphologically identified as T. b. brasiliensis. The resulting phylogenies identified two major clades that are congruent with the geographical populations studied. Based on collection sites and in accordance with type-location, one clade was identified as the subspecies T. b. macromelasoma. The second clade grouped T. b. brasiliensis populations. Restriction endonuclease sites were observed in the sequences and used in PCR-RFLP assays, producing distinct fingerprints for T. b. macromelasoma and T. b. brasiliensis populations. The results suggest that these are different species and that gene flow occurs only among T. b. brasiliensis populations, possibly associated with human activity in the area.